Knee Imaging - Osimani, Marcello; Chillemi, Claudio (Springer Milan : Imprint: Springer, 2017)
This booklet, in A to Z format, is a succinct but wide-ranging guide to the use of MRI for investigations of the knee joint. It provides easily retrievable answers to the questions that arise frequently during daily radiological practice. All relevant injuries and disorders are covered, typically with brief descriptions of pathological and clinical characteristics, guidance on selection of imaging technique, identification of potential diagnostic clues, and highlighting of useful tips and tricks. In addition, practical, state-of-the-art information is provided on other aspects of relevance. Characteristic images are included as necessary. Knee Imaging, published within the series A-Z Notes in Radiological Practice and Reporting, will be of value for both residents and general radiologists. Beyond assisting in MR reporting, it will help examination candidates in their preparation.
Keywords: Medicine.; Radiology.; Orthopedics.; Physiotherapy.; elektronické knihy; electronic books